Publication rate of abstracts of papers and posters presented at Medical Library Association annual meetings - Harvey, Sally A (Medical Library Association, 2010)
OBJECTIVES: This study sought to ascertain the publication rate of abstracts presented at the annual meetings of the Medical Library Association (MLA) for the years of 2002 and 2003. The secondary objectives were to examine possible reasons for non-publication and factors influencing publication. METHODS: A total of 442 abstracts from both meeting years, consisting of presented papers and posters, were examined. The 2 methods used to obtain a publication rate were literature searches and an online questionnaire sent to first authors. The questionnaire also asked abstract authors about reasons for non-publication and other factors that might have influenced their decisions about whether or not to submit the project for publication. RESULTS: The overall publication rate from the survey was 26.5%, and the publication rate found via literature searching was 27.6%. The most common reason given for non-publication was time restrictions. Also notable was the large proportion of abstracts written by librarians working at universities and those having 25 or more years in the library profession. DISCUSSION: Publication rates for abstracts presented at the Medical Library Association meetings for the years studied rank at the low end in comparison with other medical professional associations. Further research into factors affecting publication may reveal ways to increase this rate.